Voicing Confidence: A Narrative Inquiry into Indonesian EFL Students' Experiences with the SpeechAce Pronunciation Tool - Mustagis, R Muhammad Satria Gyas; Muljanto, Setia (PROJECT (Professional Journal of English Education), 2026)
This qualitative investigation examined pronunciation learning experiences among four male Indonesian EFL students who obtained high scores exceeding 7.0 using SpeechAce technology within a Pronunciation Practice 2 course at Institut Pendidikan Indonesia Garut. Employing narrative inquiry methodology and Labov's analytical framework, researchers systematically analyzed self-reflection documents to understand participants' developmental journeys. Results demonstrated that learners progressed through transformative phases: encountering initial pronunciation challenges, implementing personalized learning strategies, experiencing emotional validation through high performance scores, and ultimately developing enhanced speaking confidence. A significant "validation effect" emerged whereby objective machine-generated assessments functioned as psychological catalysts reconciling subjective self-perceptions with measurable performance outcomes. Participants exhibited sophisticated metacognitive abilities by utilizing detailed phoneme-level feedback and integrating multiple learning resources beyond the technological platform. Findings revealed that pronunciation improvement occurred within an "ecology of achievement" where technology dynamically interacted with instructor guidance, pedagogical frameworks, and learners' autonomous agency. This narrative study contributes qualitative insights to Computer-Assisted Pronunciation Training research by illuminating meaning-making processes through which Indonesian EFL learners cultivated pronunciation accuracy and speaking self-assurance.